1,3-Bis[(4-nitrobenzylidene)aminooxy]propane - Dong, Wen-Kui (International Union of Crystallography, 2009)
The complete molecule of title compound, C(17)H(16)N(4)O(6), is generated by a crystallographic twofold axis. Within the molecule, the two benzene units are approximately perpendicular, making a dihedral angle of 85.91 (4)°. In the crystal, molecules are linked into a three-dimensional network by C—H⋯O hydrogen bonds and short O⋯O and N⋯O interactions, with distances of 2.998 (2) and 2.968 (3) Å, respectively.